The impact of climate variability and change on economic growth and poverty in Zambia - Thurlow, James; Zhu, Tingju; Diao, Xinshen (International Food Policy Research Institute, 2009)
We combined a hydro-crop model with a dynamic general equilibrium (DCGE) model to assess the impacts of climate variability and change on economic growth and poverty reduction in Zambia. The hydro-crop model is first used to estimate the impact of climate variability on crop yields over the past three decades and such analysis is done at the crop level for each of Zambia’s five agroecological zones, supported by the identification of zonal-level extreme weather events using a drought index analysis. Agricultural production is then disaggregated into these five agroelcological zones in the DCGE model. Drawing on the hydro-crop model results at crop level across the five zones, a series of simulations are designed using the DCGE model to assess the impact of climate variability on economic growth and poverty. We find that climate variability costs the country US$4.3 billion over a 10-year period. These losses reach as high as US$7.1 billion under Zambia’s worst rainfall scenario. Moreover, most of the negative impacts of climate variability occur in the southern and central regions of the country, where food insecurity is most vulnerable to climate shocks. Overall, climate variability keeps 300,000 people below the national poverty line by 2016. A similar method is also used to examine the potential impact of climate change on the economy based on projections of a well-known global climate model and two hypothetical scenarios. We find that the effects of current patterns of climate variability dominate over those of potential climate change in the near future (until 2025). Differences in assumptions regarding rainfall changes influence both the size (to a large degree) and direction (to a lesser extent) of the economic impact of climate change. If rainfall declines by 15 percent, then climate change enhances the negative effects of climate variability by a factor of 1.5 and pushes an additional 30,000 people below the poverty line over a 10-year period. Moreover, the effects of climate change and variability compound each other, with the number of poor people rising to 74,000 if climate change is coupled with Zambia’s worst 10-year historical rainfall pattern.